The Use of Kahoot Application in Comprehending Figurative Language - Chan, Al Maghvirah; Asri, Dhiant (Vivid: Journal of Language and Literature, 2023)
Smart phone as a device cannot be separated from our daily lives today. Many applications in smartphone are available to learn English language. One of them is kahoot application. The objective of this study was to compare the effectiveness of using kahoot application and traditional discussion method in learning figurative language. This was an experimental research. Two classes as control class and treatment class were observed by giving pretest and post test. Result indicated that students in the control class performed significantly better on post test than students in the treatment class. Further research needs to be conducted to combine the use of the application and conventional method.